2016
DOI: 10.1002/chem.201602006
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Triggered Cross‐Linking of DNA Duplexes by Reversible [2+2] Photocycloaddition of Styrylpyrene

Abstract: Reversible photo-cross-linking of a DNA duplex through the [2+2] photocycloaddition of styrylpyrene is reported. Styrylpyrene moieties on d-threoninol linkers were introduced into complementary positions on DNA strands. Irradiation of the styrylpyrene pair in the duplex with visible light at λ=455 nm induced a [2+2] photocycloaddition between styrylpyrenes that cross-linked the two strands of the duplex. Two diastereomers were formed after [2+2] photocycloaddition as a result of rotation of the styrylpyrene re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 78 publications
1
72
0
1
Order By: Relevance
“…As can be seen in Figure , PCA proceeded quantitatively until complete consumption of the starting dyad. In general, PCA is a reversible reaction, and complete transformation of one isomer to another is sometimes possible only if one of isomers does not absorb an incident light. However, it is not relevant to this case: 4 has low but noticeable absorbance at 370 nm (MAC=4300 M −1 cm −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen in Figure , PCA proceeded quantitatively until complete consumption of the starting dyad. In general, PCA is a reversible reaction, and complete transformation of one isomer to another is sometimes possible only if one of isomers does not absorb an incident light. However, it is not relevant to this case: 4 has low but noticeable absorbance at 370 nm (MAC=4300 M −1 cm −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…To develop long wavelength reactive photoreactions that can be operated in a sensitive biological environment without adverse effect on cells and tissues, recent studies have focused on the development of chromophores that can absorb light in the visible region 38–43. In particular, our group has reported the activation of [4+4] cycloadditions under visible light irradiation using an electron‐rich anthracene moiety38 by substitution of a triazole group at the 9‐position.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a pair of stirylpyrenes that react upon visible light irradiation. 33 We also demonstrated that pairs of cyanostilbene improve the stability and enzymatic durability of siRNA. Fluorescent labeling of DNA or RNA has been widely used in biology and biotechnology, but most fluorophores are quenched by nucleobases through electronhole transfer.…”
Section: Cationic and Photocrosslinking Pairsmentioning
confidence: 74%